Structural shear joints analyses, properties and design for repeat loading - Hahn, George T. (American Society of Mechanical Engineers, 2005)
This book describes the mechanical response of butt, lap and doubler joints. The findings apply to shear connections in civil, aerospace, and other mechanical structures subjected to repeated loading. The findings are intended for engineers and NDE practitioners concerned with the design of new, as well as inspection and maintenance of existing shear joints